Social Disorganization Theory and Crime Rates on California Community College Campuses. Issue 1 (2nd January 2017) - Ravalin, Tamara; Tevis, Tenisha
ABSTRACT: Recent media attention concerning the escalation of crime on college campuses has created a sense of urgency to address how crime will impact the largest community college system in the United States, California Community Colleges. Crime can deter academic success and social engagement. This study utilizes social disorganization theory to examine the impact of crime on 113 California community college campuses. To address the purpose of this research, we analyze the relationship between social structure elements, community organization factors, and crime rates using IPEDS, CCCCO Data Mart, the 2011 Clery report, and data from institutional websites. Employing social disorganization theory, we looked across multiple measures for community impact. By employing correlation and regression analyses, we found that the percentage of students receiving Pell Grants demonstrated a strong relationship with an increase in both personal and property crimes across most California community college campuses.